Evaluation of Forest Trees/Shrubs in Nun River Forest for Ornamentals towards a Greener Future - Youpkarigha, F.O.; Unanaonwi, O.E. (University of Sri Jayewardenepura 2018, 2018)
The call for a greener tomorrow is global and nothing could green the environment other than trees and plants, the conglomerate of vegetation. Most perceptions of forest and its resources centers on timber, wildlife and some non-timber forest products. Majority perceive green environment to be distant locations in the wild far away from urban settlement. However, it is known, and people ought to be aware that our cities, streets, public places, even the interior of our homes can be made green. It requires identification, selection and cultivation (ISC) of trees/plants that could be used as ornamentals- a step towards greener future. The possibility lies on the fact that every geographic region has specific tree/plant species that could be identified which if embarked upon, will underscores the barrier of inaccessibility to exotic species with the associated cost of acquisition. In most part of the tropical world with vast diversity of plant species, one could still find in fashionable or rather a sign of being on the higher strata of socioeconomic life, people placing orders for ornamental plants from the West whereas there are numerous species in the within forests unidentified. The most ideal approach to a sustained greener future is by developing the indigenous plants and using them as ornamentals. Ornamental plants are more protected than those in the wild and remain as symbols of ownership foreclosing all kinds of trespass. Ornamentals cannot be cut or remove indiscriminately being that they were purposefully planted. Forest trees do not enjoy such protection especially in most third world countries where there are no enforceable forest protection laws. Within this reality, there may be no realistic method for a greener future than identifying, selecting and cultivation of indigenous forest plants for ornamentals and urban plantings. This study aimed at identifying and selecting indigenous forest trees/shrubs in the Nun river forest for ornamentals. Identification of trees and shrubs was carried out in four randomly selected 50×10 m transect in the Nun River forest. Also, four out of ten communities about the forest were randomly selected and trees were identified and classified into indigenous and exotic species. 1,127 trees/shrubs were identified which 821 (72.85%) were exotic, while 306 (27.15%) were indigenous. Out of 306 identified indigenous trees/shrubs, 13 (4.25%) were cultivated as ornamentals in the study area. The study shows that exotic trees/shrubs were planted as ornamentals than indigenous trees in the five communities. There is need for awareness among rural communities of the vast plant resources available in our forests which has not been employed as ornamentals. A greener tomorrow begins today.
Keywords: Nun river forest, Forest community dwellers, Ornamental plants, Indigenous trees, Selection and cultivation